The Role Of E-Commerce For MSMEs - Betty Rahayu (FEB Universitas Maritim Semarang, 2023)
The purpose of this research is to determine the determinants of choice variables for MSME companies in Cimahi when it comes to using e-commerce. In this study, the Theory of Planned Behavior (TPB) is used as a theoretical framework to construct research hypotheses. The earliest stages of the research began with the collection of primary data in the form of questionnaire responses from Cimahi chips SMEs, with a total of 148 respondents filling out the questionnaire. The acquired data will next be processed using various linear regression methods. According to the findings of the study, Cimahi chip SMEs have a favorable attitude toward e-commerce adoption. They also include the influence of social norms as a factor to consider when adopting e-commerce. Perceived behavioral control influences e-commerce adoption as well. Based on the findings of the research, footwear MSMEs that have not used e-commerce should analyze the benefits of e-commerce for business, while MSMEs that have used e-commerce can assess the benefits and restrictions of utilizing e-commerce. The government can also help MSMEs adopt e-commerce by giving training, constructing suitable infrastructure, and establishing applicable legislation.